PENYULUHAN HUKUM TENTANG HAK PILIH PEMILIH PEMULA BAGI ANAK YANG MENGGUNAKAN HAK POLITIKNYA - Muzayanah Muzayanah (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2021)
Community Service Activities are the implementation of the Tri Dharma of Higher Education which must be carried out in order to provide understanding to the community, especially for the "SITI KHADIDJAH" Orphanage Children, Semarang City. This community service activity really needs to be given in order to provide legal counseling about "The Right to Vote for Beginner Voters for Children Who Use Their Political Rights". Towards the implementation of the 2024 General Election which will be held by all citizens of the Republic of Indonesia, it is very necessary to give an understanding of the responsibilities, rights and obligations as citizens of the state to participate in implementing the democratic process, so that it is necessary to raise public legal awareness of obedience to the law. the applicable law, in this case to use voting rights in voting for Beginner Voters, in this case the children of the Orphanage who already have Voting Rights as Beginner Voters. This legal counseling really needs to be given considering that the children in the "Siti Khadidjah" Orphanage are the majority of children with the criteria as Beginner Voters in exercising their political rights by voting in the Presidential and Vice-Presidential Elections as well as in the Election of Legislative Members both Central and Regions as well as Regional Head Elections which are held every 5 (five) years in the change of leadership of both the Executive and Legislative Institutions. This legal counseling is given so that children as Beginner Voters have a positive response and participate in exercising their voting rights so that the implementation of democracy in Indonesia continues well, so that the administration of state administration in government can be carried out based on the 1945 Constitution of the Republic of Indonesia. Given the majority children do not understand and understand about the political rights regulated in the 1945 Constitution, especially Article 27 Paragraph (2) that: Every citizen has the same position in law and government and is obliged to uphold the law of government with no exceptions, then the meaning contained in the "concurrent position in government" it can be understood that every citizen is obliged and has the right to administer the government. The political rights possessed by children as beginner voters are very decisive in the success of the democratic process in Indonesia, because the voting rights granted by children are very significant. This legal counseling was carried out prior to the COVID-19 emergency response. It is hoped that with this counseling, children as Beginner Voters exercise their political rights and do not act Golput (White Group) or do not vote during the General Election due to not understanding their political rights, so it is hoped that the orphanage children will have optimism in nation and state life.